Linear array of loop antennas with serial excitation and quasi-isotropic radiation pattern in the electric plane - T. N. Parfenovich; O. A. Yurtsev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results of numerical modeling of linear array of loop antennas with perimeter length equal to two wavelengths on a central frequency are given. Frames are bent in the electric plane to produce electrical quasi-isotropic directivity pattern in this plane and are serial interconnected.